The Interplay of Brand Image, Brand Trust, and Customer Satisfaction in Building Customer Loyalty of Sustainable Skincare Products Among College Students - Yanti, Kadek Oktaria Vina; Basmantra, Ida Nyoman (Transpublika Publisher, 2025)
The rapid growth of the sustainable skincare industry and increasing competition have made it challenging for brands to maintain long-term loyalty, particularly among young and environmentally conscious consumers. Despite rising awareness of sustainability, empirical evidence explaining the psychological mechanisms underlying loyalty in this segment remains limited. This study investigates the influence of brand image and brand trust on customer loyalty, with customer satisfaction functioning as a mediating variable, focusing on sustainable skincare products among college students in Indonesia. A quantitative research design was employed, utilizing a structured questionnaire administered to college students who actively use sustainable skincare products. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among the study variables. The results reveal that brand image and brand trust exert positive and significant effects on customer satisfaction. Moreover, customer satisfaction significantly impacts customer loyalty and serves as a mediating mechanism between brand image, brand trust, and customer loyalty. These findings underscore the central role of customer satisfaction in translating brand-related attributes into enduring customer loyalty. The study novelty of lies in the development of an integrated mediation model that contextualizes brand image and brand trust within the sustainable skincare industry targeting Indonesian college students, a segment that has received limited scholarly attention. The study contributes to the literature on brand loyalty and sustainable consumer behavior and provides practical insights for sustainable skincare companies to strengthen loyalty by enhancing brand image, trust, and customer satisfaction in a highly competitive market.